2018
DOI: 10.1002/arch.21477
|View full text |Cite
|
Sign up to set email alerts
|

Pheromone‐binding proteins in the Asian gypsy moth females, Lymantria dispar, recognizing the sex pheromone and plant volatiles

Abstract: Lepidopterans are known to have different pheromone-binding proteins with differential expression patterns that facilitate specific signal transduction of semiochemicals. Two PBPs of the Asian gypsy moth, Lymantria dispar, were reported to express in both females and males, but their physiological functions were unknown. Results showed that LdisPBP1 and LdisPBP2 were expressed in the sensilla trichodea of males and the s. trichodea and s. basiconica of females. When LdisPBP1 gene was targeted by RNA interferen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…As a robust functional genomics tool, successful RNAi experiments have been conducted in numerous lepidopteran species including L. dispar (Terenius et al, 2011;Kim et al, 2015;Lin et al, 2015;Xu et al, 2016;Yu et al, 2018;Sun et al, 2019) (Table 1). To investigate the function of Ldmthl1, we employed RNAi technology to knockdown the expression of Ldmthl1 in the 3 rd instar L. dispar larvae.…”
Section: Ldmthl1 Rnai Decreased Deltamethrin Sensitivity and Suppressmentioning
confidence: 99%
“…As a robust functional genomics tool, successful RNAi experiments have been conducted in numerous lepidopteran species including L. dispar (Terenius et al, 2011;Kim et al, 2015;Lin et al, 2015;Xu et al, 2016;Yu et al, 2018;Sun et al, 2019) (Table 1). To investigate the function of Ldmthl1, we employed RNAi technology to knockdown the expression of Ldmthl1 in the 3 rd instar L. dispar larvae.…”
Section: Ldmthl1 Rnai Decreased Deltamethrin Sensitivity and Suppressmentioning
confidence: 99%
“…The PBPs are believed to recognize the pheromone constituents, whereas members in the GOBP group are considered to recognize ‘general’ odorants such as host plant volatiles ( Zhou 2010 ). However, many studies have also demonstrated that PBPs are able to recognize volatiles from host plants and GOBPs have a strong affinity for sex pheromone constituents ( Liu et al 2015a , Khuhro et al 2017 , Yu et al 2018 , Sun et al 2019 ). PBPs and GOBPs are both belong to ‘classic OBP’ group, and the remarkable feature of classic OBPs is the presence of six positionally conserved cysteine residues ( Zhou 2010 , Pelosi et al 2014 , Brito et al 2016 ).…”
mentioning
confidence: 99%
“…Supraphysiological concentrations of pheromone can evoke some neuronal activity [56], indicating that while LUSH may play a role in delivering cVA to the cognate receptor (OR67d), it is not an integral part of the signal transduction machinery. Recent in vivo work in moths has yielded similar results, with genetic knockdown or knockout of pheromone-binding OBPs resulting in 20-60% reductions in global pheromone-evoked antennal electrical activity [57][58][59][60][61][62][63] and similar decreases in behavioural responses [57,59,61,63]. The more modest phenotypes observed in moths relative to those in D. melanogaster may be due to methodological differences of these studies, but could also reflect functional redundancy between co-expressed moth OBPs [57].…”
Section: Non-receptor Proteins In Olfactory Signalling Pathwaysmentioning
confidence: 71%